Sexual dysfunction in women with Parkinson's disease. Issue 11 (8th August 2016) - Varanda, Sara; Ribeiro da Silva, Joana; Costa, Ana Sofia; Amorim de Carvalho, Cristiana; Alves, José Nuno; Rodrigues, Margarida; Carneiro, Gisela
Abstract: Background: Sexual dysfunction in women with Parkinson's disease is poorly understood and research in this area is scarce. The objectives of this study were sexual function characterization in female Parkinson's disease patients, description of sexual dysfunctions, correlation with disease characteristics, and comparison with matched healthy controls. Methods: Social and demographic data from consecutive female patients with Parkinson's disease and matched healthy controls were collected. The following instruments were used: UPDRS, the Hoehn and Yahr scale, the Beck Depression Inventory‐II, the Female Sexual Function Index, and the Sexual Dysfunction Inventory. The only exclusion criterion was cognitive deterioration precluding comprehension of the study scope and its instruments. Results: Of the 95 patients identified, 61 were included. Mean age was 66 years (range 40—89 years), and mean disease duration was seven years (range 1‐18 years). Twenty‐nine presented an akinetic‐rigid syndrome, 25 tremoric disease, and, the remaining, a mixed type of disease. Mean "on" total/part III UPDRS scores were 46 ± 15.0 and 31 ± 8.9. Sexual dysfunction was present in 86.9% of patients and 79.0% of controls, according to the Female Sexual Function Index ( p  < .01), and in 57.4% of patients and 22.6% of controls, according to the Sexual Dysfunction Inventory ( p  < .001). Multivariate binary logistic regression identified age and depressive symptoms as positive predictors in the severity of sexual dysfunction. Disease duration, UPDRS part III score, Hoehn and Yahr stage, and antiparkinsonian medication did not show significant predictive value. Conclusions: Sexual dysfunction is more prevalent in women with Parkinson's disease than in controls and is predicted by older age and severity of depressive symptoms. © 2016 International Parkinson and Movement Disorder Society